Precision Planning in Autotransplantation of Teeth by Using CBCT – An Effective Prosthetic Approach - Shrestha, Prabhat; Shrestha, P (Journal of Nepalese Prosthodontic Society, 2019)
Auto transplantation can be considered a valid and predictable treatment option for rehabilitating patients with permanent teeth loss when a suitable donor tooth is present. Once thought to have unfavorable prognosis, auto transplantation has achieved high success rates and is an outstanding option for tooth replacement. This case report illustrates auto transplantation of a fully developed third molar in the place of a first molar with the guidance of CBCT (Cone Beam Computed Tomography).The added advantages of CBCT helps to make the process of auto transplantation more predictable, easier and less time consuming which will encourage many dental surgeons to add this treatment to their armamentarium.